Dicarbanonaborates in yeast respiration and membrane transport - Kotyk, A; Lapathitis, G (Biochemistry and molecular biology international, 1997)
Two derivatives of carborates, sodium 5,6-dichloro-7,8-dicarbanonaborate (CB-Cl) and sodium 5-mercapto-7,8-dicarbanonaborate (CB-SH) were found to inhibit endogenous as well as glucose-induced respiration of the yeast Saccharomyces cerevisiae. Both substances slightly increased endogenous acid production, were neutral toward H(+)-ATPase-associated acidification but pronouncedly inhibited the K(+)-stimulated acidification. The same effects were observed also with an ATPase-deficient mutant of the yeast. The ATP-hydrolyzing activity of yeast plasma membranes in vitro was severely reduced. The membrane potential was substantially increased toward more negative values. The H(+)-symporting uptake of glutamic acid was considerably decreased, that of adenine was diminished much less. The effects of the dicarbanonaborates are obviously pleiotropic but their inhibition of ATP hydrolysis and of uptake of H(+)-symported substances, on the one hand, and absolute lack of effect on ATPase-catalyzed acidification, on the other, pose an unresolved problem.
Keywords: boritany; Saccharomyces cerevisiae; aktivní transport; Oxygen Consumption; adenosintrifosfát; Adenosine Triphosphate; Biological Transport, Active; Proton-Translocating ATPases; protonové ATPasy; Borates; spotřeba kyslíku